Tabulation and landscape characters of Lenggong Valley's Malay traditional houses / Mohd Ruzaini Che Zahari and Wan Yusrizal Wan Ibrahim - Che Zahari, Mohd Ruzaini; Wan Ibrahim, Wan Yusrizal (UiTM Press, 2024)
Lenggong Valley is famously known as an archaeological site due to UNESCO's World Heritage Site verification. Following this, the aspiration towards Global Geopark recognition comprising Lenggong's distinctive cultural heritage was initiated. Malay traditional house is one of the attributes of cultural heritage. It presents a character that symbolises uniqueness reflected in the states where they were built and the relation between historical events. This study aims to explore the distribution tabulation and landscape characters of Malay traditional houses in Lenggong Valley, Perak, Malaysia. The methodology includes site observation and evaluation, with the spatial location of the houses recorded using GPS. The collected samples of hundred eight (108) traditional houses were analysed using Kernel Density Analysis. Results showed that the tabulation of Lenggong traditional houses is concentrated approximately to caves and the Perak River concurrence with the historical evidence of Paleolithic human settlement and the Malay sultanate era. Two (2) significant types of traditional houses found are Rumah Limas Bumbung Perak (RLBP) with 79% and Rumah Kutai (RK) with 14%. Most of the houses are still preserved with vernacular architecture and semi-vernacular which points to their significant identity. The landscape of the traditional houses also points to the unique characters supported by the geographical setting of Lenggong as a valley. These findings support the aspiration of a Geo- Park in Lenggong in the context of the cultural heritage landscape and provide substantial information to authorities regarding conservation and preservation of Lenggong as a heritage cultural site in a broader sense. Future study is encouraged to provide a detailed assessment of the houses' condition towards heritage preservation and conservation efforts.